Neutron powder diffraction study of Pb[Zrx(Fe2/3W1/3)1–x]O3 solid solutions. Issue 6 (9th February 2015) - Frantti, J.; Fujioka, Y.; Zhang, J.; Zhu, J.; Vogel, S. C.
<x xml:space="preserve">Abstract</x> This study presents the structural and magnetic properties of solid solutions Pb[Zrx(Fe2/3W1/3)1−x]O3 (PZFW), with x = 0.35 and 0.60. The focus is on the study of magnetic ordering and the co‐existing electrical dipole moments as a function of temperature. Neutron powder diffraction (NPD) measurements showed that both samples possess a pseudo‐cubic structure. A G‐type antiferromagnetic (AFM) order onsets at around 150 K in PZFW with x = 0.35, accompanied by a broad hump in the magnetization, magnetic peak width determined from the NPD patterns, and thermal expansion versus temperature curve, which indicate a diffusive phase transition. Weak anomalous thermal expansion was assigned to the spontaneous magnetostriction. A susceptibility cusp characteristic to an AFM ordering was observed at 15 K though no evident change was observed in the NPD patterns at 12 K. The magnetic behavior is assigned to different size clusters: with decreasing temperature a larger fraction of the material becomes magnetically ordered. Remnant magnetization was observed in PZFW with x = 0.35 at 2 K. No magnetic reflections were seen in PZFW with x = 0.60 down to 12 K. Magnetometer measurements revealed a weak AFM cusp at 8 K, confirmed by hysteresis loop measurements. The off‐center Pb‐displacements and the oxygen octahedra displacement along the cubic axis with respect to the B‐cations generate an electric dipole moment.